Primary Health Networks' impact on Aboriginal Community Controlled Health Services. Issue 1 (7th December 2018) - Coombs, David
Abstract: The Abbott government's creation of Primary Health Networks in 2015 has substantially affected the way that primary healthcare funding is administered at the Commonwealth level. Primary Health Networks control a significant amount of Indigenous‐specific health funding, which Aboriginal Community Controlled Health Services have historically relied upon. These Indigenous sector organisations have been delivering holistic and culturally appropriate healthcare to Aboriginal and Torres Strait Islander people for decades. They are run by and for Aboriginal Communities themselves, enacting Indigenous self‐determination at a local level. The Primary Health Networks promote contestable funding and competitive service markets, destabilising the Indigenous health funding environment. This new funding model does not account for the distinguishing feature of Aboriginal Community Controlled Health Services: self‐determination. Additionally, Primary Health Networks possess limited knowledge of Indigenous health contexts and have been resistant to engagement with Aboriginal organisations. All of this limits Indigenous self‐determination and threatens Indigenous health. Abstract : This article examines how the Primary Health Networks (PHNs) – recently created health funding administrators – have affected Indigenous self‐determination. Based on interviews with Aboriginal Community Controlled Health Services the article concludes that PHNs limit Indigenous Communities' agency in the provision of Indigenous health services, thus constraining Indigenous self‐determination.